STRUCTURAL INVESTIGATION OF THE INTERMEDIATE LAYER IN A BIMETAL MILL ROLLER PRODUCED BY THE METHOD OF VERTICAL AXIS CENTRIFUGAL CASTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Subject of the investigation is a bimetallic mill roller with external, working layer from high chromium material and inner, supporting layer from ductile cast iron. The processes, accompanying the formation of a transition layer in bimetallic castings, produced by centrifugal casting have been investigated. Attention has paid to the structural changes in the transition zone, caused by the diffusion processes occurring during the casting and crystallization.